Improving the well-being of families of children with Autism Spectrum Disorder (ASD) in Internally Displaced People (IDP) camps in South East and North Central Nigeria - Ezenwanne, Dorothy Nkem (Humanities Horizon, 2025)
The well-being of families of children with Autism Spectrum Disorder (ASD) in Internally Displaced People (IDP) camps in South East and North Central Nigeria is an area of increasing concern. The study utilized descriptive survey design, and the target population consisted of 80 parents and caregivers from camps in Anambra, Enugu, Imo, Benue, Kogi, and Nasarawa. A simple random sampling method was used for participant selection. Data were collected through a structured, validated questionnaire, with reliability confirmed via a Cronbach’s Alpha coefficient of 0.76. Descriptive and inferential statistics, including ANOVA, were used for data analysis. The findings highlight significant healthcare issues, such as a lack of specialists, inaccessible diagnostic services, and scarce medication. In education, challenges include the absence of tailored curricula, inadequate facilities, and exclusion from learning activities. Additionally, the study identifies key strategies to address these issues, including the provision of specialized caregiver training, the establishment of therapy centers, financial support, community awareness campaigns, and peer support groups. The study concludes that addressing these challenges requires comprehensive and coordinated efforts involving government, NGOs, and local communities to improve the overall well-being of these vulnerable families. The results provide valuable insights for policy development and program implementation in humanitarian settings, ensuring better support and inclusion for children with ASD.